Patient Satisfaction and Their Willingness to Pay for a Pharmacist Counseling Session in Hospital and Community Pharmacies in Saudi Healthcare Settings - AlShayban, Dhfer Mahdi; Naqvi, Atta Abbas; Islam, Md. Ashraful; Almaskeen, Mohammed; Almulla, Ali; Alali, Muhab; AlQaroos, Abdullah; Raafat, Mohamed; Iqbal, Muhammad Shahid; Haseeb, Abdul (Frontiers in Pharmacology, 2020)
Objective Patient satisfaction is an indicator for quality of healthcare service and is sometimes linked to patients’ willingness to pay. Willingness to pay is an economic method for estimating patient’s inclination for a service in monetary terms. This study assessed satisfaction of patients from pharmacist counseling service and estimated their willing to pay for the same. Methods A month-long survey was conducted in community and hospital pharmacies located in Khobar, Dammam and Qatif cities of Saudi Arabia, using Arabic version of Patient Satisfaction Feedback (PSF) questionnaire. Convenient sampling method was used, and sample size was calculated based on power analysis. Data was analysed through SPSS version 23. Chi-square test and regression analyses were conducted to report associations between variables and, determinants of satisfaction as well as willingness to pay respectively. The study was ethically approved (IRB-2019-05-020). Results Patients (n = 531) with previous counseling experience were more likely to be satisfied (AOR 5.2, p<0.05). Patients were more willing to pay if, they had an income above SAR 10,000 i.e., USD 2666.5 (AOR 1.78, p<0.05), were satisfied with counseling time duration (AOR 4.5) and, were able to get counseling without difficulty (AOR 2.1, p<0.05). Patients were more likely to be satisfied and were willing to pay if, they received required knowledge/information completely (AOR 2.5, 3.7 & p<0.05) and found pharmacist helpful (AOR 1, 4.5 & p<0.05). Most patients (43.9%) were satisfied with pharmacist counseling and average satisfaction rating was 7.87±1.99/10. Conclusion Patients considered counseling as an important service and were satisfied from it. However, less than a third of patients were willing to pay for the service. Knowledge and helpfulness of pharmacist were identified as two major determinants that could not only satisfy and but also promote willingness to pay for the service. A pharmacist with skills in pharmaceutical care and counseling could be useful in promoting the service and even commercializing it in future.